VARIASI METODE PEMBELAJARAN IPA PADA HOMESCHOOLING KAK SETO PEKANBARU - Sepriance Sepriance; Said Suhil Achmad; Sumardi Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this research is to discover how variations in learning methods are implemented by Professor Kak Seto Homeschooling Pekanbaru and Knowing the general state of social situations in Kak Seto Homeschooling. This research uses descriptive methods with a qualitative approach. The research topics in this study were 3 people data collection techniques using interviews, observation and documentation. Data analysis techniques using triangulation. The results of the research method used by the question-and-answer conference in accordance with the material taught to the residents of the learning. Tutors use a variety of learning methods to simplify the teaching and learning process so that citizens do not get bored. The Kak Seto Homeschooling learning method is to use a more thematic, active, creative and fun approach and independent learning with a focus on life skills and problem-solving skills. For this reason, the learning process at Kak Seto Homeschooling is fun and not focused on academics.Key Words: Variations in learning methods, learning methods.